Diskursus Eksistensialisme Sartre dalam Vedānta - I Gede Arya Juni Arta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Existentialism is not just a philosophy that studies the existence of humans, but places human as the main existence. Sartre can be said to be the central figure in this philosophy, which states that existence precedes essence. In his ontology, Sartre strictly divides étre-en-soi (Being-in-itself) and étre-pour-soi (Being-for-inself). Where the first is created objects without consciousness, and the second is human with counsciousness. According to Sartre, humans want to be both étre-en-soi and étre-pour-soi, that is to be perfect, but they cannot. Perfection (étre-en-soi-étre-pour-soi) belong to God. Sartre’s pessimism can be traced through the Vedānta discourse, which optimistically states that human nature is perpect, and humans are capable of making themselves perfect.